PERAN INTERNATIONAL MARITIME ORGANIZATION (IMO) DALAM PEMBERDAYAAN PEREMPUAN DI KOMUNITAS MARITIM MALAYSIA - Fitriani "; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study examines the role of imo in empowering women, especially in the Malaysian maritime community. Comprehensive maritime industry policies that can be adequately monitored to achieve competitive advantage are important. Malaysia's maritime industry is made up of multiple sectors regulated by fragmented government bodies. In this study, the researcher attempts to analyze the Malaysian maritime industry cluster which consists of three main sectors: Shipping, Ship Industry, Ports and Terminals.The Strength Indicator Model has been developed to reveal maritime industry clusters. The author finds that the factors of Competition, Location, Connection, Government, and Opportunity affect the ability of Malaysian maritime industry clusters. The result of this research is the existence of a framework for the Regulatory Body and various stakeholders to support the progress of the Malaysian maritime industry towards the development of a more competitive and sustainable industry with the aim of becoming a developed maritime country.The method used in this research is qualitative research with descriptive method. The level of analysis used is the level of analysis of the nation-state group, so that the perspective used is feminist and uses international organization theory.Keywords: Rule Theory, IMO, Feminist, Maritime Community.